Development of a Blended Learning Model Based on Edmodo for PKL Students in Vocational High Schools - Cahyono, Budhi; Amanulloh, Rivkih; Warso, Warso; Ngisomudin, Ngisomudin; Ayundha, Titania Allin (Journal of Vocational Education Studies, 2026)
The purpose of this study was to develop an Edmodo-based blended learning model for street vendors in vocational high schools, analyze the feasibility of the model, and test its effectiveness. The study was conducted at SMK Muhammadiyah Sampang, Cilacap Regency, using a research and development (R&D) method based on the ADDIE model. The research design used a one-group pretest-posttest design. The development procedure included analysis, design, development, implementation, and evaluation stages. In the analysis stage, a student needs survey was conducted, while the design stage was adjusted to the learning needs. The next stage of development included validation by experts on the model and materials, and then the product was revised. Implementation was carried out on 60 students of grade XI in the Light Vehicle Engineering study program. The research results show that Edmodo-based blended learning is suitable as an alternative learning model, particularly to support internship activities. This model can be implemented according to a plan consisting of orientation, organization, investigation, analysis, and evaluation. In terms of effectiveness, student learning outcomes with Edmodo-based blended learning achieved an average of above 80, significantly different from the group not using Edmodo. Furthermore, this model can increase student motivation and learning independence. Based on these findings, the study recommends further development of the Edmodo-based blended learning model as a complement to face-to-face learning, especially in normative and adaptive subjects in vocational high schools.